PERANCANGAN HOTEL RESORT DI PANTAI KETAWANG KABUPATEN PURWOREJO DENGAN PEDEKATAN ARSITEKTUR TROPIS - Septian Priatna; Sri Kurniasih; Karya Subagya (MAESTRO, 2022)
Tourism has an important role for the economic growth of a region. One of the tourist destinations that is currently in great demand by tourists when enjoying holidays is the beach. There is an area that has the natural beauty of a typical big wave area, namely Ketawang beach. This tourist attraction is located in Tawangrejo Village, Grabag District, Purworejo Regency. However, there is no accommodation facility for Resort Hotels on Ketawang Beach to support the completeness of the accommodation on this Ketawang Beach. Considering the increasing number of visitors in Purworejo Regency, especially on this Tawang Beach every year and the potential for its natural beauty. Therefore, the purpose of building a resort hotel in this area is to attract more tourists who visit these tourist attractions in order to make this Ketawang beach tourism object more known by local tourists and foreign tourists and provide comfort and safety for visiting tourists.